2011
DOI: 10.1007/s11062-011-9168-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin E on Blood-Brain Barrier Permeability in Aged Rats with PTZ-Induced Convulsions

Abstract: The effect of vitamin E on the blood-brain barrier (BBB) permeability was studied under conditions of pentylenetetrazole (PTZ)-induced convulsions in aged (23-to 24-month-old) male albino rats; Evans Blue was used as a tracer. The BBB permeability was found to considerably increase in rats with PTZ-evoked seizures; the Evans Blue contents in the left and right hemispheres and cerebellum + brainstem region were significantly higher than those in the control. Vitamin E used in the dose of 70 mg/kg exerted practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Animal studies have shown the importance of Vitamin E in a dose-dependent manner as a protective factor for BBB permeability and have demonstrated that the dose dependence of this antioxidant in aged animals differs from that in younger organisms [84]. In this context, it is worth mentioning that previous studies have shown that the deficiency in vitamin E increases brain tissue oxidative stress and impairs the integrity of the blood-brain barrier, which may have relevance to the pathogenesis of amyotrophic lateral sclerosis and other neurological diseases [85].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Animal studies have shown the importance of Vitamin E in a dose-dependent manner as a protective factor for BBB permeability and have demonstrated that the dose dependence of this antioxidant in aged animals differs from that in younger organisms [84]. In this context, it is worth mentioning that previous studies have shown that the deficiency in vitamin E increases brain tissue oxidative stress and impairs the integrity of the blood-brain barrier, which may have relevance to the pathogenesis of amyotrophic lateral sclerosis and other neurological diseases [85].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Similarly, we get the same results for VIV. Moreover, both NAI and VIV cross the BBB [ 37 38 ], it means roles of NAI and VIV similar to the role of E20, GNT, THA, and HUP. Hopefully, NAI is a natural multiple inhibitors for multiple enzymes among A20, ACE, AChE, BACE1, BCHE, ChAT, CYLD, CYP1A1, GSK3β, IDE, MARK, MM-2, NEP, and PP2A.…”
Section: Resultsmentioning
confidence: 99%
“…21 AT increases the permeability of blood brain barrier in streptozotocin induced convulsions in albino rats and spare the action on NPY release to attain the anticonvulsant effect of NPY. 22 AT, in any form, inhibits oxidation of low density lipoproteins and decreases phenomenon of thromboembolism and clot formation and hence decreases heart attacks. When it is given in combination with ascorbic acid (AA) and carotenoids provides safer and effective results.…”
Section: Discussionmentioning
confidence: 99%